A Fluorescent Activatable AND‐Gate Chemokine CCL2 Enables In Vivo Detection of Metastasis‐Associated Macrophages. Issue 47 (11th October 2019) - Fernandez, Antonio; Thompson, Emily J.; Pollard, Jeffrey W.; Kitamura, Takanori; Vendrell, Marc
Abstract: We report the novel chemical design of fluorescent activatable chemokines as highly specific functional probes for imaging subpopulations of immune cells in live tumours. Activatable chemokines behave as AND‐gates since they emit only after receptor binding and intracellular activation, showing enhanced selectivity over existing agents. We have applied this strategy to produce mCCL2‐MAF as the first probe for in vivo detection of metastasis‐associated macrophages in a preclinical model of lung metastasis. This strategy will accelerate the preparation of new chemokine‐based probes for imaging immune cell function in tumours. Abstract : Live show : Fluorescent activatable chemokines have been designed as the first chemical probes for in vivo detection of tumour‐associated macrophages in lung metastasis. Activatable chemokines behave as AND gates since they emit only after receptor binding and intracellular activation, thereby showing enhanced selectivity over existing agents.